Characterization of mortars with iron ore tailings using destructive and nondestructive tests. (30th January 2017) - Carrasco, E.V.M.; Magalhaes, M.D.C.; Santos, W.J.D.; Alves, R.C.; Mantilla, J.N.R.
Highlights: IOTs have the potential to be used as a fine aggregate because they are relatively inert. The possibility of using IOTs in place of fine aggregate in the production of rendering mortars is a significant achievement. The mechanical wave propagation method is used to determine the mechanical properties of the resulting mortars. The determination of the static and dynamic Young's modulus of IOT mortars are presented using destructive and non-destructive tests. High-performance mortars can be produced not only as rendering material but also as structural material in building construction. Abstract: Although several researchers have been working on the mechanical and physical characterization of iron-ore tailings (IOT) in order to consider the possibility of using this material to replace natural aggregate in the preparation of mortars, they have not investigated the dynamic and static modulus of elasticity of IOT mortars yet. Therefore, the main goal of this study is to present an experimental investigation on the determination of the static and dynamic Young's modulus of IOT mortars using destructive and non-destructive tests respectively. It is also presented the correlation between the IOT mortar static (Eci ) and dynamic (E) elasticity modulus. It is seen that 88% of the observed variation in the elasticity modulus is attributable to the approximate linear relationship between the dynamic and static values, a very impressive result. The results indicate that it is possible to obtain high-performance mortars to be used not only as rendering material but also as structural material in building construction.